Highly efficient nondoped blue organic light-emitting diodes with high brightness and negligible efficiency roll-off based on anthracene-triazine derivatives. Issue 47 (23rd October 2019) - Liu, Futong; Man, Xiaxia; Liu, Hui; Min, Jiarui; Zhao, Shiyuan; Min, Wenrong; Gao, Lei; Jin, Haixu; Lu, Ping
Abstract : A nondoped device based on the PIAnTAZ emitter shows blue electroluminescence with a maximum EQE of 7.96%, a maximum luminance of 58 675 cd m −2 and negligible efficiency roll-offs. Abstract : Achieving highly efficient blue emitters at high luminance with nondoped structure is a crucial issue in the field of commercial full-color organic light-emitting diodes (OLEDs). In this paper, we designed and synthesized three novel blue materials PIAnTAZ, TPAAnTAZ and CzAnTAZ by utilizing anthracene as the primary acceptor, triazine as the assistant acceptor and phenanthroimidazole/triphenylamine/carbazole as the donor. The nondoped device based on the PIAnTAZ emitter exhibits blue electroluminescence with an emission peak at 468 nm, a maximum luminance over 50 000 cd m −2 and a maximum external quantum efficiency (EQE) of 7.96%. More importantly, the nondoped device exhibits an ultra-low efficiency roll-off of 7.90% at a high luminance of up to 1000 cd m −2 ; even at a brightness of 10 000 cd m −2, the EQE can still remain as high as 6.49%. This work provides a new insight into the design of high-efficiency OLEDs at high luminance with simple device structure for further practical applications.